Lipid composition of the brains of she-goat and castrated goat consumed in Ekiti State, Nigeria - Adeyeye, EI; Adesina, AJ (Bangladesh Journal of Scientific and Industrial Research, 2015)
The levels of fatty acids, phospholipids and sterols were determined in the brains of she-goat and castrated goat found in Ekiti State, Nigeria by gas chromatography. Results showed that the crude fat levels were 9.98 and 10.2 % in the brains of she-goat and castrated goat respectively. The fatty acid composition of she-goat and castrated goat brain shows that the SFA was 40.6 and 42.7 %, MUFA was 37.1 and 38.7 % and PUFA was 20.9 and 22.3% respectively. The other parameters of she-goat and castrated goat brain were found: PUFA/SFA, 0.490 and 0.548; MUFA/SFA, 0.869 and 0.953; n-6/n-3, 0.775 and 11.7; LA/ALA, 0.876 and 28.0; AA/DGLA, 6.05 and 17.4; EPA/DHA, 1.00 and 5.89 and EPSI (PUFA/MUFA), 0.564 and 0.575 respectively. Phospholipids were present in she-goat and castrated goat with a value range of 2365 and 3047 mg/100g respectively. Among the sterols, only cholesterol was of any significant level with values of 1353 mg/100g (she-goat brain) and 1355 mg/100g (castrated goat brain). Linear correlation at ? = 0.05, df: n-1 showed that no significant difference exists between the crude fats, phospholipids and sterols except in the fatty acids parameters. Bangladesh J. Sci. Ind. Res. 50(2), 153-162, 2015